Negative image construal in the media - Kushneruk, Svetlana (Przegląd Wschodnioeuropejski, 2021)
This present paper upholds discursive aspects of image construal in British news media. The term negative image construal is introduced within the framework of World Modelling Theory, developed by the author to explore discourse in terms of representational structures. The objective is to reveal news content that contributes to negative image construal. Discourse-world of information war is characterized as a conceptually complex representational structure, textualized in the British media. It is argued that negative country image of Russia is profiled against a background of discourse-world of information war. This enables media managers to evaluate Russia as adversary of the West. The materials are taken from the “News on the Web” corpus, covering the period of 2010-2018.